The collective work of teachers and students at the Catholic University of ereira (2021)
The collective work of teachers and students is the result of the pedagogical culture of the University, which renews the curriculum dimension around the integration and the problem teaching knowledge. Through the experience that this pedagogical practice raises, a relationship of teaching-learning is based progressively, through formulation, implementation and shared evaluation of the formation process in all its dimensions and development. In this document a reflection is made on the pedagogical horizon and the curricular foundations of the collective work; it is argued about its relationship with the professional teaching practice, the educational research and the university research system. Also some guidelines and commitments are defined for the collective work at the institutional level.